Marine turtles technical report - Miller, Jeffrey Dean (Kingdom of Saudi Arabia Meteorological & Environmental Protection Administration, 1989)
contents: vol.1 An assessment of the conservation status of marine turtles in Saudi Arabia. vol. 2 Recommendations for the conservation of marine turtles in the Kingdom of Saudi Arabiaa.
Keywords: Management; Wildlife conservation; Sea turtles